The Uniqueness of the Chinese Mission Movement—Past, Present, and Future - Ho, Mary (International bulletin of mission research, 2022)
Using the World Christian Encyclopedia, 3rd edition (WCE-3) as the springboard, this article explores the uniqueness of the Chinese missions movement from China, not including the overseas Chinese diaspora or Taiwan, Hong Kong, and Singapore. First, we provide an overview, context, and backdrop of the Chinese missions movement. Second, we compare and contrast China’s missions sending with that of (1) the United States/United Kingdom and (2) Brazil. We then highlight the unique characteristics of the Chinese missions movement and conclude with a future outlook.